Komunikasi Visual Kampanye Kesadaran Anak Dewasa Awal Mendukung Ibu pada Fase Sarang Kosong - Elserisa, Lily (SPACEPRO: Product Design Jurnal, 2023)
Abstract The empty nest phase is experienced by the mother in middle adulthood (40-60 years) when the children leave the house and start a new life. This phase creates feelings of discomfort for the mother and has psychological implications. If there’s no proper coping mechanism it can interfere physical health of the mother as well. Social support from children in the form of intensive communication is needed in undergoing this phase. This study aims to design a visual communication awareness campaign for early adulthood supporting mothers in empty nests. This design was carried out using the Design Thinking method (Brown, 2008) which was combined with a message delivery strategy and media selection (Kasilo, 2008) with three major stages: inspiration, ideation, and implementation. The result of the design is visual communication for the awareness campaign entitled “Keluar Sarang” through the media: Instagram Story content, comics in Instagram Multiple Posts, ambient media plates, posters, clothes hangers, mugs, sticker packs, and pillows that are persuasive, communicative, and synergistic. Keywords: Awareness Campaign, Empty Nest Syndrome, Illustration, Visual Communication.